Study on Preparation Process and Performance of Tungsten-based Uranium Nitride Microspheres Dispersed Fuel - LIU Wentao1, 2, DU Jiangping1, 2, ZHAO Yumeng1, 2, MA Chunyu2, LIU Wei1, 2, CAI Zhenfang2 (Yuanzineng kexue jishu, 2024)
CERMET dispersion fuel is currently a hotspot in the research and development of fuels for nuclear thermal propulsion (NTP) reactors. Uranium nitride (UN) has a uranium density 40% greater than that of uranium dioxide (UO2), as well as the advantages of high thermal conductivity and good resistance to irradiation. But the melting point of UN is relatively low compared to that of UO2, and it has a large linear coefficient of thermal expansion. If UN fuel is purely used, it will greatly limit the operating temperature of the reactor core, thus reducing the NTP specific impulse. Tungsten has the advantages of high melting point, high thermal conductivity, and low linear coefficient of thermal expansion, which can make up for the shortcomings in the thermal performance of UN fuel. Meanwhile, to further enhance the loading capacity of the dispersed fuel, the structure of the UN dispersed fuel is designed in the form of microspheres. The advantages of the two materials complement each other, so that tungsten-based UN microspheres dispersed fuel can be obtained, which is an ideal material for space NTP system. In this work, the preparation of UN microspheres as well as tungsten-based UN microsphere dispersed fuel pellets was successfully realized by adopting the process route of carbothermal reduction-nitriding, cold press molding, and pressureless hydrogen sintering. The effects of different parameters on the preparation effect of the UN microspheres and pellets were investigated, and the properties of the UN microspheres and pellets were also characterized and analyzed. It is found that the UN microspheres have the highest purity of 93.79% and the relative density of 96%T.D., when the carbonization temperature is 1 900 ℃ and the holding time is 8 h, and the nitriding temperature is 1 900 ℃ and the holding time is 3 h. The wet mixing and drying of UN microspheres using propylene tritol as binder and anhydrous ethanol as diluent can make the distribution of UN microspheres in the pressed pellets more uniform; and the densification sintering using a hydrogen atmosphere can result in a high densification density of 95%T.D. or more. The performance test results of the UN microspheres and pellet samples show that, the microspheres in the tungsten-based UN pellets are complete and uniformly distributed, the distribution of N and U elements in the microspheres is also uniform, and the interfaces between the tungsten matrix and the UN microspheres are tightly adhered without obvious delamination. The thermal conductivity of the pellets gradually decreases with the increase of temperature, and the thermal conductivity is 182.6 W/(m·K) at 100 ℃.